Expression of the human iImmunodeficiency virus type-1 coreceptors CXCR-4 (fusin, LESTR) and CKR-5 in CD34+ hematopoietic progenitor cells - Deichmann, Martin; Kronenwett, Ralf; Haas, Rainer (Blood, 1997)
CD34+ hematopoietic progenitor cells were assessed for mRNA expression of the human immunodeficiency virus type-1 (HIV-1) coreceptors CXCR-4, also termed fusin or LESTR, and CKR-5, also called CC-CKR-5 or CCR-5. The CD34+ cells were obtained from leukapheresis products of 17 patients after granulocyte colony-stimulating factor-supported cytotoxic chemotherapy. Using a two-step enrichment procedure including immunomagnetic bead separation and fluorescence-activated cell sorting, the CD34+ cells had a median purity of 99.8%. Assessing 9 CD34+ cell samples by polymerase chain reaction after reverse transcription (RT-PCR), CXCR-4 mRNA was found in all samples, whereas CKR-5 mRNA was only present in 3 samples, even though a nested PCR was used. Eight additional CD34+ cell samples were sorted according to CD4 expression. Based on a three-color immunofluorescence analysis, the mean relative fluorescence intensity of HLA-DR was smaller on CD34+/CD4+ cells in comparison with CD34+/CD4− cells. CXCR-4 mRNA was found in 5 of 8 CD34+/CD4+ samples and in 7 of 8 CD34+/CD4− samples, whereas CKR-5 mRNA was detected in 2 CD34+/CD4+ samples and in 1 CD34+/CD4− cell sample. Looking at the total number of CD34+ cell samples examined, the proportion of specimens containing CXCR-4 mRNA was 84% in comparison with 24% of specimens positive for CKR-5 mRNA. These data suggest that CD34+/CD4+ hematopoietic progenitor cells, including true stem cell candidates, could be susceptible to HIV-1 infection. Considering the relatively low incidence of CD34+ cell samples containing CKR-5 mRNA, CD34+/CD4+ cells appear to be particularly prone for HIV-1 infection via the CXCR-4 coreceptor. Because this chemokine receptor allows T-cell-tropic HIV-1 strains to infect cells, CD34+ cells expressing CD4 and CXCR-4 might be infected by HIV-1 during later stages of the disease, following a viral phenotype switch from macrophage- to T-cell-tropic HIV-1 strains.